PAHs content in sunflower, soybean and virgin olive oils: Evaluation in commercial samples and during refining process - Vitor Hugo Teixeira (2007)
Polycyclic aromatic hydrocarbons (PAHs) are environmental carcinogenic compounds that may contaminate vegetable oils and their levels can be reduced by refining. In order to understand the influence of the refining steps, the content of 15 PAHs was assessed throughout alkaline refining in soybean, sunflower and olive oil samples. Eight commercial brands of these oils were also analysed. The analytical method involved a liquid-liquid extraction, a solid-phase clean up (C-18 and Florisil) followed by RP-HPLC with fluorimetric detection. The total PAHs content in the studied samples can be considered generally low. The light PAHs (2-4 rings) were predominant. Virgin olive oils showed the highest values (max. 26 mu g/kg). An evident decrease of PAHs contents during alkaline refining was observed (71%, 88% and 85% in sunflower, soybean and olive oils, respectively) being more pronounced in light PAHs. Neutralization and, particularly, deodorization were the more effective steps contributing to the PAHs decrease. Bleaching was responsible for a slight increase in the PAHs content in soybean and olive oils.